Pemanfaatan Satwa Liar sebagai Obat Tradisional di Desa Air Mesu Timur dan Cambai Selatan, Kabupaten Bangka Tengah - Sujadi Priyansah; Randi Syafutra; Fifin Fitriana; Ririn Apriyani; Elvan Hatta Mahatir; Mardiana Safitri; Tri Dimas Husin (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2021)
Bangka is one of the main islands in Bangka Belitung Islands Province whose people still believe in local culture that has been passed down for generations. Community of Air Mesu Timur and Cambai Selatan Villages, Bangka Tengah District still believe it. Air Mesu Timur and Cambai Selatan Villages are two of several villages that surround Gunung Mangkol Great Forest Park. This study aimed to find out the usage of wild animals as traditional medicine by the community of Air Mesu Timur and Cambai Selatan Villages, which wild animals they used, and how they processed it. The method used was snowball sampling which consists of a preliminary survey and informant gathering, and the interview to gather the information and data collection. Ten species of wild animals were used by the community as traditional medicine. The wild animals were obtained from hunting in Gunung Mangkol Great Forest Park. Currently, people who use wild animals as traditional medicine have decreased due to the existence of modern medicine and the decline of the wild animal population. However, in small groups, people still use wild animals as traditional medicine.